Establishing the concept of aza-[3 + 3] annulations using enones as a key expansion of this unified strategy in alkaloid synthesis - Gerasyuto, Aleksey I.; Ma, Zhi-Xiong; Buchanan, Grant S.; Hsung, Richard P. (Beilstein Journal of Organic Chemistry, 2013)
A successful enone version of an intramolecular aza-[3 + 3] annulation reaction is described here. Use of piperidinium trifluoroacetate salt as the catalyst and toluene as the solvent appears to be critical for a successful annulation. We also demonstrated for the first time that microwave irradiation can accelerate aza-[3 + 3] annulation reactions. An attempt to expand the scope of the enone aza-[3 + 3] annulation was made in the form of propyleine synthesis as a proof of concept. While synthesis of the enone annulation precursor was successfully accomplished, the annulation proved to be challenging and was only modestly successful.
Keywords: alkaloids synthesis; catalysis; enones; intramolecular aza-[3 + 3] annulation; N-heterocycles; natural product; vinylogous amides

(untitled) - Harrity, J. P. A.; Provoost, O. (Org. Biomol. Chem., 2005)
See for a leading review on hetero-[3 +3] annulations.

(untitled) - Hsung, R. P.; Kurdyumov, A. V.; Sydorenko, N. (Eur. J. Org. Chem., 2005)
See for a leading review on hetero-[3 +3] annulations.

(untitled) - Buchanan, G. S.; Feltenberger, J. B.; Hsung, R. P. (Curr. Org. Synth., 2010)
See for a leading review on aza-[3 +3] annulations.

(untitled) - Lawrence, A. K.; Gademann, K. (Synthesis, 2008)
See for a leading review on aza-[3 +3] annulations.

(untitled) - Sklenicka, H. M.; Shen, H. C.; Wei, L.-L.; Zehnder, L. R.; McLaughlin, M. J.; Hsung, R. P. (Trends Heterocycl. Chem., 2001)

Strategies and Tactics in Organic Synthesis - Hsung, R. P.; Cole, K. P. (The Total Synthesis of (-)-Arisugacin A, 2004)

(untitled) - Tang, Y.; Oppenheimer, J.; Song, Z.; You, L.; Zhang, X.; Hsung, R. P. (Tetrahedron, 2006)

(untitled) - Hsung, R. P.; Wei, L.-L.; Sklenicka, H. M.; Douglas, C. J.; McLaughlin, M. J.; Mulder, J. A.; Yao, L. J. (Org. Lett., 1999)
See for method development.

(untitled) - Sklenicka, H. M.; Hsung, R. P.; Wei, L.-L.; McLaughlin, M. J.; Gerasyuto, A. I.; Degen, S. J. (Org. Lett., 2000)

(untitled) - McLaughlin, M. J.; Hsung, R. P.; Cole, K. C.; Hahn, J. M.; Wang, J. (Org. Lett., 2002)

(untitled) - Sydorenko, N.; Hsung, R. P.; Darwish, O. S.; Hahn, J. M.; Liu, J. (J. Org. Chem., 2004)

(untitled) - Gerasyuto, A. I.; Hsung, R. P.; Sydorenko, N.; Slafer, B. W. (J. Org. Chem., 2005)

(untitled) - Sydorenko, N.; Hsung, R. P.; Vera, E. L. (Org. Lett., 2006)

(untitled) - Ghosh, S. K.; Buchanan, G. S.; Long, Q. A.; Wei, Y.; Al-Rashid, Z. F.; Sklenicka, H. M.; Hsung, R. P. (Tetrahedron, 2008)

(untitled) - Buchanan, G. S.; Dai, H.; Hsung, R. P.; Gerasyuto, A. I.; Schienebeck, C. M. (Org. Lett., 2011)

(untitled) - Wei, L.-L.; Hsung, R. P.; Sklenicka, H. M.; Gerasyuto, A. I. (Angew. Chem., Int. Ed., 2001)
See for investigations related to intramolecular annulations.

(untitled) - Sklenicka, H. M.; Hsung, R. P.; McLaughlin, M. J.; Wei, L.-L.; Gerasyuto, A. I.; Brennessel, W. W. (J. Am. Chem. Soc., 2002)

(untitled) - Iaroshenko, V. O.; Ali, S.; Babar, T. M.; Dudkin, S.; Mkrtchyan, S.; Rama, N. H.; Villinge, A.; Langer, P. (Tetrahedron Lett., 2011)
See for recent studies in aza-annulations.

(untitled) - Guo, H.; Xu, Q.; Kwon, O. (J. Am. Chem. Soc., 2009)

(untitled) - Jeanne Alladoum, J.; Toum, V.; Hebbe, S.; Kadouri-Puchot, C.; Dechoux, L. (Tetrahedron Lett., 2009)

(untitled) - Zhong, W.; Lin, F.; Chen, R.; Su, W. (Synthesis, 2008)

(untitled) - Hayashi, Y.; Gotoh, H.; Masui, R.; Ishikawa, H. (Angew. Chem., Int. Ed., 2008)

(untitled) - Mancey, N. C.; Butlin, R. J.; Harrity, J. P. A. (Synlett, 2008)

(untitled) - Trost, B. M.; Dong, G. (Org. Lett., 2007)

(untitled) - Provoost, O. Y.; Hazelwood, A. J.; Harrity, J. P. A. (Beilstein J. Org. Chem., 2007)

(untitled) - Luo, S.; Zificsak, C. A.; Hsung, R. P. (Org. Lett., 2003)
See for natural product synthesis using the intramolecular annulation.

(untitled) - Sydorenko, N.; Zificsak, C. A.; Gerasyuto, A. I.; Hsung, R. P. (Org. Biomol. Chem., 2005)

(untitled) - Swidorski, J. J.; Wang, J.; Hsung, R. P. (Org. Lett., 2006)

(untitled) - Wang, J.; Swidorski, J. J.; Sydorenko, N.; Hsung, R. P.; Coverdale, H. A.; Kuyava, J. M.; Liu, J. (Heterocycles, 2006)

(untitled) - Gerasyuto, A. I.; Hsung, R. P. (Org. Lett., 2006)

(untitled) - Gerasyuto, A. I.; Hsung, R. P. (J. Org. Chem., 2007)

(untitled) - Zhang, Y.; Gerasyuto, A. I.; Long, Q. A.; Hsung, R. P. (Synlett, 2009)

(untitled) - Robinson, R. (J. Chem. Soc., 1917)

(untitled) - Boger, D. L. (Chem. Rev., 1986)

(untitled) - Boger, D. L. (Tetrahedron, 1983)

Comprehensive Organic Synthesis - Trost, B. M.; Fleming, I. (Pergamon Press, 1991)
See chapters on cycloaddition reactions.

(untitled) - Happ, G. M.; Eisner, T. (Science, 1961)
See for leading reviews on azaphenalene alkaloids.

(untitled) - King, A. G.; Meinwald, J. (Chem. Rev., 1996)

(untitled) - Stevens, R. V. (Acc. Chem. Res., 1984)

(untitled) - Tursch, B.; Daloze, D.; Dupont, M.; Pasteels, J. M.; Tricot, M.-C. (Experientia, 1971)
See for isolations of azaphenalene alkaloids.

(untitled) - Karlsson, R.; Losman, D. (J. Chem. Soc., Chem. Commun., 1972)

(untitled) - Tursch, B.; Daloze, D.; Pasteels, J. M.; Cravador, A.; Braekman, J. C.; Hootele, C.; Zimmermann, D. (Bull. Soc. Chim. Belg., 1972)

(untitled) - Tursch, B.; Daloze, D.; Braekman, J. C.; Hootele, C.; Cravador, A.; Losman, D.; Karlsson, R. (Tetrahedron Lett., 1974)

(untitled) - Tursch, B.; Daloze, D.; Braekman, J. C.; Hootele, C.; Pasteels, J. M. (Tetrahedron, 1975)

(untitled) - Tursch, B.; Daloze, D.; Hootele, C. (Chimia, 1972)
See for isolation of propyleine.

(untitled) - Moore, B. P.; Brown, W. V. (Insect Biochem., 1978)

(untitled) - Mueller, R. H.; Thompson, M. E. (Tetrahedron Lett., 1980)
See for a total synthesis of propyleine.

(untitled) - Ma, X.; Gang, D. R. (Nat. Prod. Rep., 2004)
See for leading reviews on lycopodium alkaloids.

(untitled) - Ayer, W. A. (Nat. Prod. Rep., 1991)

The Alkaloids - MacLean, D. B. (Academic Press, 1985)

The Plant Alkaloids - Henry, T. A. (The Blackiston Company, 1949)

The Isoquinoline Alkaloids. Chemistry and Pharmacology - Shamma, M. (Academic Press, 1972)

The Chemistry and Biology of Isoquinoline Alkaloids - Brown, R. T. (Springer-Verlag, 1985)

The Alkaloids. Chemistry and Biology - Szántay, C. (Academic Press, 1998)

(untitled) - Rapoport, H.; Windgassen, R. J.; Hughes, N. A.; Onak, T. P. (J. Am. Chem. Soc., 1960)

(untitled) - Janot, M.-M. (Tetrahedron, 1961)

(untitled) - Wiegrebe, W.; Kramer, W. J.; Shamma, M. (J. Nat. Prod., 1984)

The Merck Index: An Encyclopedia of Chemicals, Drugs, and Biologicals - Budavari, S.; O’Neil, M. J.; Smith, A.; Heckelman, P. E.; Kinneary, J. F. (Merck and Co. Inc., 1996)

Critical Care Medicine. Principles of Diagnosis and Management in the Adult - Zimmerman, J. L.; Rudis, M. (Chapter 73, 2002)

(untitled) - Ma, W.-W.; Anderson, J. E.; McKenzie, A. T.; Byrn, S. R.; McLaughlin, J. L.; Hudson, M. S. (J. Nat. Prod., 1990)

(untitled) - Bose, D. S.; Kumar, R. K. (Heterocycles, 2006)
See for an account on the use of microwaves in aza-[3 + 3] annulations.

(untitled) - Kang, Y.; Mei, Y.; Du, Y.; Jin, Z. (Org. Lett., 2003)
See for an account on the use of microwaves in oxa-[3 + 3] annulations.

(untitled) - Karstens, W. F. J.; Stol, M.; Rutjes, F. P. J. T.; Kooijman, H.; Spek, A. L.; Hiemstra, H. (J. Organomet. Chem., 2001)

(untitled) - Esch, P. M.; Hiemstra, H.; Klaver, W. J.; Speckamp, W. N. (Heterocycles, 1987)

(untitled) - Evans, D. A.; Thomas, E. W.; Cherpeck, R. E. (J. Am. Chem. Soc., 1982)

(untitled) - Parikh, J. R.; Doering, W. v. E. (J. Am. Chem. Soc., 1967)